History and memory in the Dead Sea Scrolls remembering the teacher of righteousness - Williams, Travis B. 1980- (New York Cambridge University Press, 2019)
Charts a new methodological course in Dead Sea Scrolls scholarship by employing memory theory to inform historical research.
Cover -- Half-title page -- Title page -- Copyright page -- Dedication -- Contents -- Tables -- Acknowledgments -- Abbreviations -- 1 Introduction -- 1.1 The Traditional Perspective on the Teacher of Righteousness -- 1.2 The New Perspective on the Teacher of Righteousness -- 1.2.1 The Theoretical Framework of the New Perspective -- 1.2.2 The Interpretive Focus of the New Perspective -- 1.2.2.1 An Audience-Oriented Approach -- 1.2.2.2 A Historical Approach -- 1.3 Purpose of the Study -- PART I METHODOLOGICAL CONSIDERATIONS -- 2 A Theoretical Approach toward History -- 2.1 The Scientific Approach toward Historiography -- 2.2 The Postmodern Critique of Scientific Historiography -- 2.2.1 Poststructuralist Postmodernism -- 2.2.2 Challenging the Tenets of Scientific Historiography -- 2.2.3 Responses to the Postmodern Critique -- 2.3 Scientific Historiography after the Postmodern Critique -- 2.3.1 Objectivity within Historiography -- 2.3.2 Representation and Truth -- 2.4 Historiography and the Teacher Materials -- 2.4.1 The Historical Potential of the Ancient Sources -- 2.4.2 The Perspectival Nature of the Ancient Sources -- 2.4.3 The Interpretive Categories of the Ancient Sources -- 2.5 Conclusion -- 3 A Mnemonic Approach toward History -- 3.1 Toward an Understanding of Memory Theory -- 3.1.1 The Origins of Collective Memory (Maurice Halbwachs) -- 3.1.2 The Cultural Dimensions of Memory (Jan Assmann) -- 3.1.3 Memory's Connection with the Past (Barry Schwartz) -- 3.2 The Relationship between History and Memory -- 3.2.1 Modern Perspectives on the History-Memory Relationship -- 3.2.2 The Complimentary Functions of History and Memory -- 3.3 Approaching History through Memory -- 3.3.1 Previous Attempts -- 3.3.2 A Mnemonic-Historical Approach -- PART II THE CIRCUMSTANCES OF MEMORY -- 4 Dating the Teacher and the Sources.
Description based on publisher supplied metadata and other sources
Keywords: Dead Sea scrolls.-4Q-Criticism, interpretation, etc; Dead Sea scrolls-Criticism, interpretation, etc; Damascus document-Criticism, interpretation, etc; Teacher of Righteousness; Electronic books